Neuronal nitric oxide synthase (NOS I) in the buffalo epididymis - E. Langella; V. Esposito; M. Sammarco; G. Scala (Italian Journal of Animal Science, 2010)
The localization of neuronal nitric oxide (NOS I) in the buffalo epididymis have been investigated by nicotinamide adenite dinucleotide phosphatase-diaphorase (NADPH-d) histochemichemistry to the light microscope (LM) and NOS immunoistochemistry to the scanning electron microscope (SEM), respectively. Histochemistry: examination of epididymis specimens revealed an intense NADPH-d staining in the basal cell epithelium and endothelium cells of blood vessel. The NADPH diaphorase staining was diffuse and granular only along the caput epididymal epithelium. NADPH diaphorase staining was less intense or absent in the corpus and in the cauda of epididymis. Dense NADPH diaphorase is labeling in the endothelium of blood vessels along the whole buffalo epididymis. Immunoistochemistry: intense NOS I immunoreactivity was detected in the caput epididymis specimen by immuno-SEM. The basal epithelium showed intense and wide-spread immunoreactivity. In the corpus and in the cauda of the epididymis not observed NOS I immunoreactivity. The specific localization of NOS I in buffalo epididymis suggest that nitric oxide may be involved to explain epididymal function: maturation and storage.